Piano Sonatas. London: Augener & Co., (ed. Mandyczewski), vol. 1 - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Mandyczewski, Eusebius, 1857-1929 (editor):::Contributor::::::::::::; Nottebohm, Gustav, 1817-1882:::Contributor:::::::::::: (London; Augener & Co.; United Kingdom, 2024)
Volume 1 of the collected edition of Beethoven's piano sonatas in a critical revision by Eusebius Mandyczewski from notes by Gustav Nottebohm and published by Augener & Co. in London and G. Schirmer in New York.